Determining the Readiness Status of University Students in STEM Education and Distance Education Course - Natalia A. Zaitseva (Kassel University Press, 2021)
This research, Science, Technology, Engineering, Mathematics (STEM) and remote training on information given and university students in STEM, and distance education classes integration on the emphasis and work, STEM and remote training on course to integration on the information given is intended. On the other hand, STEM education and distance education with related re-search support in order to ready distance education presence, levels were in-vestigated. The study was applied during the 2020–2021 fall semester. The quantitative research method was used in the research. This research study comprises groups that have been created by 520 4th grade reading Science In-formation Teacher candidates of universities. University Students ‘STEM and Distance Education Ready presence, Survey’ was applied. Data and survey were collected online. The collected data were analysed using Statistical Package for the Social Sciences software. Research on the results based on students’ training and daily lives for technology support needs that heard, their needs education and their their lives ease it provides to the results, fur-ther STEM and related studies in the literature even more writing space font contribution will provide, also STEM Education ‘ready presence, status, re-mote training ready presence, status on by more high that the result was reached.